A 'shark'-masked electrocardiogram: case report of a Tako-Tsubo syndrome. Issue 5 (7th May 2021) - Verdoia, Monica; Viola, Orazio; Marrara, Federica; Soldà, Pier Luigi
Abstract: Background: Triangular ST-segment elevation or 'shark-fin' sign has been described as a specific indicator of acute coronary occlusion and large myocardial ischaemia, translating into poorer prognosis. However, this electrocardiographic presentation has been reported in rare cases of Tako-Tsubo syndrome and associated with more severe physical stressors and neurological involvement. Case summary: We present a rare case of a 51-year-old woman presenting with incoming epileptic attacks and concomitant pyometra. Despite controlling epilepsy with phenytoin and the surgical treatment of the infection, she developed sepsis requiring vasopressors, and thereafter sustained ventricular tachycardia and diffuse ST-segment elevation with the 'shark-fin' sign. TTC was confirmed by the documentation of normal coronary arteries and the complete recovery of wall motion abnormalities at discharge. Discussion: Heterogeneous presentation and triggering conditions often challenge the diagnosis of Tako-Tsubo syndrome. The acknowledgement of different electrocardiographic and clinical manifestations can ease the diagnosis and the successful management of these patients, whose prognosis can be extremely severe in the acute phase, if unidentified.